IMPLEMENTATION OF RESILIENCE ARCHITECTURE PRINCIPLES IN SEED BANK BUILDINGS AS A MEANS OF FOOD CRISIS PREVENTION - Jatra, Dyli Tiara; Rohmah, Fiky Nur Fadhila; Z. A, Happy Faradita; Maulana, Moch. Hanif; Hidayat, Anas (ADBE, 2025)
The food crisis has emerged as a major challenge in several regions and can spread widely, especially with the uncertainty of climate change, economic fluctuations and rapid population growth. In facing this challenge, the concept of resilience emerged as an approach to strengthen the resilience of the food system and architectural design played a role, where Seed Bank buildings functioned as a means to store valuable plant seeds to restore ecosystems and biodiversity. This research aims to assess the extent to which resilience architectural principles are applied in various Seed Bank designs across Europe., namely the Svalbard Global Seed Bank and the Millennium Seed Bank. This study employs the Dynamic Mixed Methods research approach, utilizing a Paired Comparison Rating Scale to compare various building and spatial elements/components that meet the established indicator criteria. The research findings will demonstrate how resilience architecture principles are holistically applied in the design of Seed Bank Buildings, encompassing aspects such as Efficiency and Effectiveness, Eco-tech and Sustainability, Durability, and Flexibility. This study can provide valuable guidance and comparisons for building a safe, efficient, and sustainable Seed Bank in Indonesia to overcome the food crisis that may occur in Indonesia in the future.